2022
DOI: 10.1158/2159-8290.cd-22-0024
|View full text |Cite
|
Sign up to set email alerts
|

Think Globally, Act Locally: Globalizing Precision Oncology

Abstract: Summary: Globalizing precision oncology should be a major priority for cancer care in the upcoming decades. In this issue, the K-MASTER study provides a framework for infrastructure building in East Asia illustrating the widening global potential of precision oncology. It is time to modify the precision oncology mantra: Give the right drug, to the right patient, at the right time in every country, to think globally and act locally. See related article by Park et al., p. 938 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A recent review of 84,297 oncology clinical trials from the Trialtrove database revealed that 887 (1.1%) trials used germline data for inclusion/exclusion, and most trials using germline data were conducted in the United States, Canada, and Europe versus other countries, mirroring disparities in cancer genomics data globally. 21,22 In addition, immune checkpoint inhibitor pembrolizumab is US FDA-approved for solid tumors with high tumor mutational burden (TMB-high; ≥10 mutations/megabase) or microsatellite instability (which itself leads to a high TMB). 23 It was shown recently that TMB is affected by an individual's genetic ancestry and race.…”
Section: What About Implementation and Legal Issues?mentioning
confidence: 99%
“…A recent review of 84,297 oncology clinical trials from the Trialtrove database revealed that 887 (1.1%) trials used germline data for inclusion/exclusion, and most trials using germline data were conducted in the United States, Canada, and Europe versus other countries, mirroring disparities in cancer genomics data globally. 21,22 In addition, immune checkpoint inhibitor pembrolizumab is US FDA-approved for solid tumors with high tumor mutational burden (TMB-high; ≥10 mutations/megabase) or microsatellite instability (which itself leads to a high TMB). 23 It was shown recently that TMB is affected by an individual's genetic ancestry and race.…”
Section: What About Implementation and Legal Issues?mentioning
confidence: 99%
“…In addition, there is an urgent need for global harmonization across regulatory authorities to address the substantial inequities in access to medicines. Ideally, clinical trials for new therapies should be conducted globally, for access and generalizability 46 . However, the reality is that clinical trials, including RCTs, cannot be conducted in every country to generate specific evidence for that country's population.…”
Section: Globalizing Drug Development Harmonization and Transportabilitymentioning
confidence: 99%
“…They also do not address the overarching barrier of precision medicine studies: access to a broad and representative patient population across the world. 2 Master protocols can be clunky to implement at sites due to increased cost and workload. 3 Let us take the example of the regulatory requirements of managing a master protocol at a specific site.…”
Section: Innovative Trial Designmentioning
confidence: 99%
“…The innovative protocols successfully address important design considerations but bring with them their own challenges in implementation. They also do not address the overarching barrier of precision medicine studies: access to a broad and representative patient population across the world . Master protocols can be clunky to implement at sites due to increased cost and workload .…”
Section: Innovative Trial Designmentioning
confidence: 99%